An oral history of health psychology in the UK. Issue 3 (20th April 2020) - Quinn, Francis; Chater, Angel; Morrison, Val
Abstract : Purpose: An oral history of the development of health psychology in the United Kingdom. Methods: Standard oral history methods produced interviews with 53 UK health psychologists, averaging 92 min in length. All interviewees entered the field from the 1970s to the 2000s, representing all four countries in the United Kingdom. A reconstructive mode of analysis, along with the few existing sources, was used to create a narrative of the history of health psychology in the United Kingdom. Audio recordings and transcripts will be archived for use by future researchers. Findings: In the 1970s, medical schools in London recruited psychologists to teach, while also conducting pragmatic research on issues in healthcare. At the same time, some clinical psychologists began to work with physical health conditions in general hospitals. Partly influenced by developments in the United States and Europe, an identity of 'health psychology' developed and spread to researchers and practitioners doing work in psychology and health. In the 1980s, the field continued to attract researchers, including social psychologists working with health behaviours and outcomes, and clinical psychologists working in health care settings. During this time, it became formalized as a scientific field with the creation of the BPS Health Psychology Section, courses, and journals. In the 1990s, the field moved towards professional practice, which was controversial with other BPS divisions. However, it continued to grow and develop through the 2000s and 2010s. Conclusion: Reflections on the development of UK health psychology represent the first historical narrative produced from oral testimony of those who were present at the time. Statement of Contribution What is already known on this subject? Health psychology emerged in the 1970s, initially in the United States following an APA Task Force report. It developed from a range of precursor movements including psychosomatic medicine, while in the United Kingdom medical psychology was an additional precursor. The development of health psychology has been discussed for a range of countries including the United States and others, but historical scholarship relating to the United Kingdom has been limited. What does this study add? From an oral history project, a narrative of UK health psychology's development is built up. Influences included opportunities at medical schools from the 1970s onward. Growing interest in health behaviours as a test of social psychology theory was important. The experiences of clinical psychologists working in health care settings are demonstrated. Multidisciplinary influences on the emergence and shaping of health psychology are evident.